1992
DOI: 10.1128/jcm.30.8.1948-1952.1992
|View full text |Cite
|
Sign up to set email alerts
|

Staphylococcus lugdunensis endocarditis

Abstract: Staphylococcus lugdunensis is a recently described coagulase-negative species which has been associated with human infections, including infective endocarditis. A case of native valve endocarditis caused by this organism is described. The initial laboratory detection of S. lugdunensis is facilitated by a positive test for ornithine decarboxylase. The identification of such isolates should not cause difficulty unless undue reliance is placed upon a small number of tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
18
0
1

Year Published

1993
1993
2005
2005

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(20 citation statements)
references
References 23 publications
1
18
0
1
Order By: Relevance
“…S lugdunensis is a virulent organism, and our patients protracted illness was consistent with this. Although there are no documented cases of right-sided endocarditis, the mortality rate of S lugdunensis mitral valve endocarditis is approximately 50% (3,6). Our patient's successful outcome was in keeping with the general trend of better survival in cases of right-sided endocarditis.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…S lugdunensis is a virulent organism, and our patients protracted illness was consistent with this. Although there are no documented cases of right-sided endocarditis, the mortality rate of S lugdunensis mitral valve endocarditis is approximately 50% (3,6). Our patient's successful outcome was in keeping with the general trend of better survival in cases of right-sided endocarditis.…”
Section: Discussionsupporting
confidence: 73%
“…In one study, 85% of isolates were considered pathogens. It has been implicated in infections of the skin (4), brain (5), bone (5), peritoneum (5), and prosthesis (5) and left-sided heart valves (3,6). After searching MEDLINE, we have found that our case is the first documented episode of tricuspid valve endocarditis caused by this virulent organism.…”
Section: Discussionmentioning
confidence: 88%
“…Occasionally, CoNS other than S. epidermidis, S. haemolyticus, and S. hominis cause serious infections (8,14), and in certain infections, such as shunt-associated meningitis and endocarditis, beta-lactam drugs are the preferred therapy. Susceptibility tests will define all CoNS for which the oxacillin MIC is Ն0.5 mg/liter as methicillin resistant, regardless of the species and the status of the mecA gene.…”
Section: Discussionmentioning
confidence: 99%
“…13.14 In addition, S lugdunensis can have weak production of thermostable DNase. 10,13,14 Use of the "API Staph gallery" may identify the strains as Staphylococcus hominis, since acid can be produced from lactose, maltose, fructose, trehalose, and sucrose and not from mannitol and xylitol. However, S lugdunensis differs from both S aureus and S hominis by ornithine decarboxylase activity.…”
Section: Discussionmentioning
confidence: 99%